Vinylation of Carbonyl Oxygen in 4-Hydroxycoumarin: Synthesis of Heteroarylated Vinyl Ethers - Chatterjee, Rana; Santra, Sougata; Zyryanov, Grigory V.; Majee, Adinath (Synthesis, 2019)
The unique nucleophilic character of the carbonyl oxygen of 4-hydroxy coumarin has been observed by the BF3·OEt2 catalyzed reaction of 4-hydroxycoumarin and alkynes. The reactions of 4-hydroxycoumarin and substituted 4-hydroxycoumarin with various terminal alkynes have been studied. In case of internal alkyne (prop-1-yn-1-ylbenzene), the reaction with 4-hydroxycoumarin led to the corresponding product with an E/Z ratio of 3:1. This protocol is operationally very simple and has much potential for the synthesis of heteroarylated vinyl ethers from basic chemicals.
Keywords: 2-(vinyloxy)-4H-chromen-4-one; O-vinylation; 4-hydroxy coumarin; alkynes; solvent-free